HIV-positive migrants' experience of living in Sweden. Issue 1 (31st December 2020) - Mehdiyar, Manijeh; Andersson, Rune; Hjelm, Katarina
ABSTRACT: Background : There is a limited knowledge of the impact of being human immunodeficiency virus (HIV)-positive on migrants living in Sweden. It is therefore important to gain a general awareness of this issue in order to maintain the wellbeing of this vulnerable group of patients and to develop an adequate social support network. Objective : The aim of this study was to explore HIV-positive migrants' experiences of their life situations, living in Sweden. Method : A qualitative, exploratory study was performed using semi-structured interviews with 14 HIV-positive migrants, aged 29–55 years, and analyzed with qualitative content analysis. The participants were recruited from three clinics for infectious diseases in western Sweden. Results : The results are presented in the following three categories: ´Vulnerability in social relationships', 'Fear of disclosure", and ' Resilience'. The results illustrated the participants' experiences of vulnerability in their social relationships, fear of disclosing HIV status, feeling lonely and stigmatized, and lacking social network and support. Furthermore, the results illustrated participants' challenges in finding a partner, due to their fear of being recognized because of their HIV-infection. However, the result indicated participants' struggling for a normal life with integrity, and that their need to look positively at life. Conclusions : In the actual study loneliness, fear of disclosure, perceived stigma, and the lack of a social network had significant impact on the life situations of the HIV positive migrants. Fear of disclosure and the challenge of finding a partner and friends were the main obstacles. It is crucial to increase access for these patients to supporting networks that will promote their empowerment and trust.